(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
TVS motor company is one of the leading bike manufacturers in India. The analysis of the paper was based on customer’s point of view. For the study, both primary data and secondary data were required. The primary data was collected based on a survey research, using a structured questionnaire with both open ended and closed-ended questions. The sampling procedure used was random sampling for the 1st objective i.e. to understand consumer needs on motorbikes. For the 2nd objective i.e. to understand the awareness levels of TVS. The mode of survey was of personal interview, where the respondents filled up the questionnaires. The secondary data was collected from business newspapers, magazines, Company brochures, journals and the Internet. The major conclusion from this study was that TVS has to improve itself to gain the 1st position in the market as it is doing well to maintain its 3rd position. TVS has a lot of work to do if it has to take lead and remain the leading manufacturer in India.